Central bank digital currency and banking: Macroeconomic benefits of a cash-like design - Jonathan Chiu; Seyed Mohammadreza Davoodalhosseini (Bank of Canada, 2021)
Should a central bank digital currency (CBDC) be issued? Should its design be cash- or depositlike? To answer these questions, we theoretically and quantitatively assess the effects of a CBDC on consumption, banking and welfare. Our model introduces new general equilibrium linkages across different types of retail transactions as well as a novel feedback effect from transactions to deposit creation. The general equilibrium effects of a CBDC are decomposed into three channels: payment efficiency, price effects and bank funding costs. We show that a cash-like CBDC is more effective than a deposit-like CBDC in promoting consumption and welfare. Interestingly, a cash-like CBDC can also crowd in banking, even in the absence of bank market power. In a calibrated model, at the maximum, a cash-like CBDC can increase bank intermediation by 5.8% and capture up to 25% of the payment market. In contrast, a depositlike CBDC can crowd out banking by up to 2.6%, thereby grabbing a market share of about 16.7%.
Keywords: E50; E58; 330; Digital currencies and fintech; Monetary policy; Monetary policy framework